2016
DOI: 10.1111/ajt.13708
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation After Ex Vivo Normothermic Machine Preservation: A Phase 1 (First-in-Man) Clinical Trial

Abstract: Joint first authors. ISRCTN 14355416.The number of donor organs suitable for liver transplantation is restricted by cold preservation and ischemia-reperfusion injury. We present the first patients transplanted using a normothermic machine perfusion (NMP) device that transports and stores an organ in a fully functioning state at 37°C. In this Phase 1 trial, organs were retrieved using standard techniques, attached to the perfusion device at the donor hospital, and transported to the implanting center in a funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
427
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(446 citation statements)
references
References 31 publications
9
427
0
10
Order By: Relevance
“…In addition to cannulating liver inflow, there are liver MP devices requiring cannulation of the hepatic outflow (44,48). Although such a circuit might be considered more sterile due to lack of contact between the perfusate and ambient air, cannulating the inferior vena cava runs the risk of provoking hepatic congestion due to outflow resistance.…”
Section: Dcdmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to cannulating liver inflow, there are liver MP devices requiring cannulation of the hepatic outflow (44,48). Although such a circuit might be considered more sterile due to lack of contact between the perfusate and ambient air, cannulating the inferior vena cava runs the risk of provoking hepatic congestion due to outflow resistance.…”
Section: Dcdmentioning
confidence: 99%
“…Indications to ex situ NMP, results and donor and recipient characteristics are quite heterogeneous. The first experiences, were performed as attempts to resuscitate very marginal grafts already discarded by most liver transplant centers (72,78) and so far, only three randomized prospective series have been reported (48,49,71). The first human liver transplant using ex situ NMP was published by the group in Birmingham in 2016 (78).…”
Section: Normothermic Liver Perfusionmentioning
confidence: 99%
“…In our opinion, total preservation time represents an overly cautious way to compare outcomes of cold stored versus NMP grafts, as it assumes that cumulative injury over time is similar with both modalities; this is hard for us to accept for metabolically functional livers actively producing bile ex vivo. Matching storage duration in both modalities would be difficult because livers require at least 4-6 h to stabilize during the NMP phase (3)(4)(5). Although extended NMP duration should be monitored closely in ongoing safety trials, accrued porcine and limited pilot clinical experience suggests that NMP duration is not a critical variable, especially when kept ≤24 h (4).…”
Section: To the Editormentioning
confidence: 99%
“…In contrast, normothermic ex vivo liver perfusion has recently been introduced into clinical practice investigating continuous NMP with near complete exclusion of SCS. The initial clinical studies demonstrated feasibility and safety (12,13).…”
Section: Introductionmentioning
confidence: 99%